ACCOUNTABILITY FOR VILLAGE FUNDS MANAGEMENT FOR CORRUPTION PREVENTION IN PATAMPANUA DISTRICT, PINRANG REGENCY - Arham Arham; Fatimah Fatimah; Azhabu Azhabu (Journal AK-99, 2022)
This study aims to identify and analyze the accountability of village funds management and its impact on corruption prevention in Patampanua District and provide information openly about transparency and accountability to the public about village fund management in the region. The data analysis technique used in this research were descriptive qualitative. The research results showed that village fund management is accountable and free from corruption. This is indicated by the involvement of the community in the implementation of village fund activities, secondly, all the resources used, both human and material, were obtained from the village itself, and thirdly, all the results of implementation activities made transparent billboards regarding the details of the funds and the size of the development.